Flexible routing and addressing for a next generation IP. - Francis, Paul (Computer communication review.)
Due to a limited address space and poor scaling of backbone routing information, the Internet Protocol (IP) is rapidly reaching the end of its useful lifetime. The Simple Internet Protocol Plus (SIPP), a proposed next generation Internet Protocol, solves these problems with larger internet layer addresses. In addition, SIPP provides a number of advanced routing and addressing capabilities including mobility, extended (variable-length) addressing, provider selection, and certain forms of multicast. These capabilities are all achieved through a single mechanism, a generalization of the IP loose source route. We argue that, for reasons of simplicity and evolvability, a single powerful mechanism to achieve a wide range of routing and addressing functions is preferable to having multiple specific mechanisms, one for each function.